Polymer and its preparation method and use

By introducing multiple hydrophobic side chains into the polyurethane thickener to form a dense hydrophobic association network, the poor thickening effect of polyurethane thickener in the aqueous resin system in the prior art and the reduced permeability after film formation is solved. The problem of this achieves efficient thickening and water resistance improvement.

CN116355169BActive Publication Date: 2025-01-03APALENE TECHNOLOGY CO LTD (SHANGHAI)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310222443.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-01-03
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

The existing polyurethane thickening agent has limited thickening effect in aqueous resin systems, and it is easy to have problems such as free, reduced permeability and mechanical properties after film formation, making it difficult to form a high-density hydrophobic association network.

Method used

The polymer with multiple hydrophobic side chains is prepared by grafting reactions to the epoxidized polyalphaolefins with long-chain fatty acids or fatty acids with photocuring reactive groups, forming a more dense hydrophobic relationship Combining the network to improve thickening efficiency.

Benefits of technology

It significantly improves the thickening efficiency of the aqueous resin system, avoids whitening on the surface of the coating, enhances the permeability and water resistance of the wet film, and improves the mechanical properties of the paint film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention provides a polymer and a preparation method and use thereof, wherein the polymer is formed by polymerization of the following components: 1) at least one monohydric alcohol, wherein the monohydric alcohol includes one or two of the compounds of formula V1 and formula V2; 2) at least one polyether polyol; and 3) at least one diisocyanate. The polymer provided by the present invention is used as a thickener in a film-forming system containing an aqueous resin to form a denser hydrophobic associative network, which can not only improve the thickening efficiency, but also improve the permeability of the wet film of the aqueous resin system and the water resistance of the dry film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fine chemical industry, in particular to a polymer and a preparation method and application thereof. Background Art

[0002] With the increasing awareness of environmental protection, countries have successively formulated strict laws and regulations to limit the emission of VOCs. It is a general trend to "switch from oil to water" in the field of resin application. In recent years, water-based resins have developed rapidly due to their low toxicity, safety, environmental protection, and convenient construction. In order to make water-based resins suitable for various coating methods (such as spraying, roller coating, brushing, etc.) and widely used in the fields of coatings, inks and adhesives, it is usually necessary to add additional thickeners to adjust the rheology. Among them, polyurethane associative thickeners (HEUR) are used for thickening water-based resin systems due to their strong thickening efficiency, good leveling and storage stability, and high gloss after film formation.

[0003] The structure of traditional polymers is extremely simple. The prepolymer is prepared by reacting excess isocyanate with polyethylene glycol, and a long-chain alkanol is used to react with the remaining isocyanate to form a terminal end, thereby preparing a linear polymer. This linear polymer has a hydrophobic group structure of a long-chain alkane at both ends, and the thickening effect in the aqueous solution is achieved through two-point association between the hydrophobic groups. The thickening effect is general.

[0004] Patents CN101633718A and CN109439056A disclose the use of chain extenders to introduce long-chain alkyl groups as hydrophobic groups in linear polyurethane thickeners, thereby improving their thickening effect. However, the method of using chain extenders to introduce hydrophobic groups in the middle of the main chain of the molecule results in low reaction activity due to the steric effect, and the molecular weight of the polyurethane thickener after chain extension is too large, making it difficult to disperse in an aqueous solution, thereby affecting its thickening effect.

[0005] CN113061224A firstly carries out a ring-opening reaction between a long-chain alkyl acid and acrylic acid glycidyl ester, and finally grafts the resultant to the end of a conventional linear polyurethane thickener, thereby introducing a photocurable reactive group C=C into the polyurethane thickener molecule. However, this method can only introduce a long hydrophobic chain at the end of the polyurethane molecule, and the density of the hydrophobic association network formed between the hydrophobic groups is insufficient, making it difficult to obtain a photocurable polyurethane thickener with high thickening efficiency.

[0006] In addition, polyurethane thickeners are often used in various water-based resin systems. After curing and film formation, the thickener molecules are free in the cured coating. There are extremely hydrophilic segments such as polyethylene glycol in the molecules. If the hydrophobic association between the thickener molecules is not tight, migration and exudation defects are likely to occur. Before film formation, they are free to the surface of the coating and produce whitening, resulting in reduced permeability. When the film-formed coating is washed by rainwater or solvents, a series of problems occur, such as decreased mechanical properties and a white appearance that is difficult to restore. Summary of the invention

[0007] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a new polymer and its preparation method and use. The present invention proposes to carry out a ring-opening reaction between an epoxidized poly-alpha olefin and a long-chain fatty acid or a fatty acid with a photocuring reactive group C=C, and then to prepare the polymers respectively through a grafting reaction. The polymers contain multiple hydrophobic side chains, and can achieve multi-point association while retaining the photocuring groups, thereby forming a denser hydrophobic association network and improving the thickening efficiency.

[0008] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.

[0009] The present invention discloses a polymer formed by polymerization of the following components:

[0010] 1) at least one monohydric alcohol, wherein the monohydric alcohol comprises one or both of a compound of formula Ⅴ1 and a compound of formula Ⅴ2:

[0011]

[0012] Wherein, R1 is a straight-chain alkyl group or a branched-chain alkyl group having 1 to 30 carbon atoms; n is an integer ≥1;

[0013] R2 is a C1-C30 straight-chain hydrocarbon group, a branched hydrocarbon group, a cyclic hydrocarbon group with or without a side chain, a C1-C30 benzene ring, an aromatic condensed ring, or an aromatic heterocycle;

[0014] 2) at least one polyether polyol;

[0015] 3) At least one diisocyanate.

[0016] Preferably, R1 is a straight chain alkyl group having 1 to 30 carbon atoms. For example, the carbon number of R1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30. More preferably, R1 is a straight chain alkyl group having 1 to 14 carbon atoms.

[0017] Preferably, n is 1 or 2.

[0018] Preferably, R2 is a C1-C30 straight chain hydrocarbon group or a branched chain hydrocarbon group.

[0019] Preferably, the monohydric alcohol is a ring-opening reaction product of an epoxidized polyalphaolefin and a carboxylic acid compound.

[0020] Preferably, the structural formula of the epoxidized poly-alpha-olefin is as shown in Formula III:

[0021]

[0022] Wherein, R1 is a straight-chain alkyl group or a branched-chain alkyl group having 1 to 30 carbon atoms; and n is an integer ≥1.

[0023] Preferably, the carboxylic acid compound has a structural formula of R2-COOH, wherein R2 is a C1-C30 straight-chain hydrocarbon group, a branched hydrocarbon group, a cyclic hydrocarbon group with or without a side chain, a C1-C30 benzene ring, an aromatic condensed ring or an aromatic heterocycle.

[0024] More preferably, the carboxylic acid compound comprises: H 23 C 11 -COOH, H 11 C6-COOH, H 31 C 15 -COOH

[0025] Preferably, the synthesis route of the monohydric alcohol is as follows,

[0026] and / or

[0027] More preferably, in order to prevent oxidation or other side reactions of the C=C double bond in the monohydric alcohol or carboxylic acid compound prepared by the reaction, an inert gas (in the present application, the inert gas refers to the gaseous elements corresponding to all Group 0 elements in the periodic table and nitrogen) can be introduced during the reaction, and the inert gas is preferably nitrogen.

[0028] More preferably, in order to prevent the C=C double bond in the monohydric alcohol or carboxylic acid compound prepared by the reaction from polymerizing prematurely, a polymerization inhibitor may be added during the reaction.

[0029] Further preferably, the polymerization inhibitor is one or more selected from 2,6-di-tert-butyl-p-cresol (BHT), p-hydroxyanisole or methylhydroquinone.

[0030] More preferably, the amount of the polymerization inhibitor is 0.05-0.5 wt % of the monomer containing the C=C double bond.

[0031] More preferably, the molar ratio of the carboxylic acid compound to the epoxidized poly-alpha-olefin is (1-1.2):1, such as 1:1, 1.1:1 or 1.2:1.

[0032] More preferably, the reaction temperature is 90-140° C., more preferably 110-140° C. For example, it may be 90° C., 100° C., 110° C., 120° C., 130° C. or 140° C. Too high a temperature may easily generate by-products, while too low a temperature may affect the reaction.

[0033] More preferably, the reaction system includes a first catalyst; the first catalyst is a quaternary ammonium salt compound.

[0034] More preferably, the quaternary ammonium salt compound is one or more selected from benzyltrimethylammonium chloride, tetrabutylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride or hexadecyltrimethylammonium chloride.

[0035] More preferably, the first catalyst is used in an amount of 0.05-0.5 wt % of the epoxidized poly-alpha-olefin. Too much catalyst will cause a waste of raw materials, while too little catalyst will affect the conversion rate of the epoxidized poly-alpha-olefin prepolymer.

[0036] More preferably, the reaction endpoint is controlled so that the acid value of the product is lower than 30 mgKOH / g.

[0037] More preferably, the reaction endpoint is controlled so that the acid value of the product is lower than 5 to 25 mgKOH / g.

[0038] More preferably, the reaction endpoint is controlled so that the acid value of the product is lower than 16-22 mgKOH / g.

[0039] Preferably, the polyether polyol comprises polyethylene glycol having a molecular weight of 400 to 20,000 g / mol.

[0040] More preferably, the polyether polyol comprises polyethylene glycol having a molecular weight of 6000 to 10000 g / mol.

[0041] Preferably, the diisocyanate is a C1-C20 straight-chain alkyl group, a branched-chain alkyl group, a cyclic alkyl group with or without a side chain, a C1-C20 benzene ring, or an aromatic condensed ring diisocyanate.

[0042] More preferably, the diisocyanate is isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), diphenylmethane-4,4'-diisocyanate or toluene-2,4-diisocyanate.

[0043] The present invention also provides a method for preparing the polymer, comprising the following steps:

[0044] 1) Polyether polyol and diisocyanate are contacted and reacted to form a prepolymer;

[0045] 2) The prepolymer is then contacted with the monohydric alcohol to generate the polymer.

[0046] Preferably, the molar ratio of the hydroxyl group in the monohydric alcohol to the isocyanate group in the prepolymer is (1-1.2):1. For example, it may be 1:1, 1.05:1, 1.0:1, 1.1:1, 1.15:1, 1.18:1, or 1.2:1.

[0047] Preferably, the reaction system includes a second catalyst; the second catalyst is one or more selected from dibutyltin dilaurate, stannous octoate or an organic bismuth catalyst.

[0048] More preferably, the organic bismuth catalyst is one or both selected from bismuth neodecanoate and bismuth 2-ethylhexanoate.

[0049] Preferably, the reaction system further comprises an organic solvent; the organic solvent is a ketone.

[0050] More preferably, the organic solvent is one or more selected from acetone, methyl ethyl ketone, and ethyl pyrrolidone.

[0051] Preferably, the reaction temperature is 60-100°C, preferably 75-95°C.

[0052] Preferably, step 2) further comprises a post-treatment step, wherein the post-treatment step comprises distillation, and the organic solvent and unreacted reactants in the reaction solution are removed by distillation under reduced pressure.

[0053] Preferably, the degree of polymerization of the prepolymer formed by the polyether polyol and the diisocyanate is 2-20.

[0054] Preferably, in order to prevent oxidation or other side reactions of the C=C double bond in the monohydric alcohol, an inert gas (in this application, inert gas refers to gaseous elements corresponding to all Group 0 elements in the periodic table and nitrogen) may be introduced during the reaction, and the inert gas is preferably nitrogen.

[0055] Preferably, in order to prevent the C=C double bond in the monohydric alcohol from polymerizing prematurely, a polymerization inhibitor may be added during the reaction.

[0056] More preferably, the polymerization inhibitor is one or more selected from 2,6-di-tert-butyl-p-cresol (BHT), p-hydroxyanisole or methylhydroquinone.

[0057] More preferably, the amount of the polymerization inhibitor is 0.05-0.5 wt % of the monomer containing the C=C double bond.

[0058] The invention also discloses the use of the polymer as a thickener in a film-forming system containing an aqueous resin.

[0059] Preferably, the water-based resin is a water-based acrylic resin, a water-based polyurethane resin, a water-based polyurethane-acrylate resin, a water-based light-curable acrylic resin, a water-based light-curable polyurethane resin or a water-based light-curable polyurethane-acrylate resin.

[0060] Preferably, the film-forming system containing the aqueous resin includes one or more of aqueous coatings, aqueous inks or aqueous adhesives.

[0061] Preferably, based on the mass of the water-based resin, the amount of the polymer is 0.1-1.0 wt%, such as 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, etc.

[0062] As described above, the present invention provides a new polymer and also provides a preparation method of the polymer, wherein a polyalphaolefin oligomer containing an unsaturated double bond is directly peroxidized to prepare an epoxidized polyalphaolefin, and the epoxidized polyalphaolefin can be subjected to a ring-opening reaction with a long-chain fatty acid or a fatty acid with a photocuring reactive group C=C, and then prepared by a grafting reaction. The polymer is used as a thickener in a film-forming system containing an aqueous resin, and belongs to a conventional polyurethane thickener and a photocuring polyurethane thickener, wherein the photocuring polyurethane thickener contains a plurality of hydrophobic side chains, and can achieve multi-point association while retaining the photocuring group, thereby improving the thickening efficiency, and the introduction of a plurality of hydrophobic side chains at the molecular end of the conventional polyurethane thickener is conducive to multi-point association to form a tighter hydrophobic association network, thereby avoiding the whitening phenomenon caused by the freeing to the paint film surface after the paint is prepared, and the length and branching degree of the hydrophobic side chain can be freely adjusted according to the length of the hydrophilic polyethylene glycol segment, thereby obtaining a polyurethane thickener with high thickening efficiency. Compared with the prior art, the preparation method is simple, the hydrophobic segment is directly synthesized in one step by polymerization reaction, the photocuring reaction active group C=C or other hydrophobic side chain is introduced by ring-opening reaction, the molecular structure of the polyurethane thickener is designed and adjusted, and conventional or photocurable polyurethane thickeners with different branching degrees and hydrophobic side chain lengths can be easily synthesized.

[0063] When the thickener is used in a film-forming system containing a water-based resin, it can significantly improve the permeability of the wet film and avoid the whitening phenomenon on the surface of the paint film after spraying, which is beneficial to color comparison and matching in practical applications. After the paint film is completely dry, it has excellent water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is the infrared spectrum of the polymer prepared in Example 7.

[0065] Figure 2 This is the infrared spectrum of the polymer prepared in Example 8.

[0066] Figure 3 This is the infrared spectrum of the polymer prepared in Example 9.

[0067] Figure 4 The following are rheological test diagrams of the polymer prepared in Example 7 at different concentrations.

[0068] Figure 5 The following are rheological test diagrams of the polymer prepared in Example 8 at different concentrations.

[0069] Figure 6 The following are rheological test diagrams of the polymer prepared in Example 9 at different concentrations.

[0070] Figure 7 The following are rheological test graphs of the polymer prepared in Example 10 at different concentrations.

[0071] Figure 8 The following are rheological test graphs of the polymer prepared in Example 11 at different concentrations.

[0072] Fig. 9 The graphs are rheological test graphs of the polymer prepared in the comparative example at different concentrations.

[0073] Fig.10 This is the rheological test diagram of the JF1025 emulsion system when the polymer is added at a dosage of 0.25wt%. DETAILED DESCRIPTION

[0074] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0075] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0076] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between the steps explicitly mentioned, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. The change or adjustment of their relative relationship shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0077] The specific embodiment of the present application provides a method for preparing a specific polymer:

[0078] (1) Epoxidized poly-alpha-olefin reacts with a carboxylic acid compound to generate a monohydric alcohol, and the preparation method is as follows:

[0079] The epoxidized poly-alpha-olefin and the carboxylic acid compound are placed in a reaction bottle, the first catalyst is added, the temperature is raised to a certain temperature, the temperature is kept for reaction for 2 hours, and then the temperature is continued to be raised, and the temperature is kept for reaction until the acid value of the sample test is lower than 30 mg KOH / g, to obtain the product monohydric alcohol.

[0080] (2) Monohydric alcohol, polyether polyol and diisocyanate are used to prepare a polymer, and the preparation method is as follows:

[0081] Add polyethylene glycol with a molecular weight of 400 to 20,000 g / mol to a reaction vessel, heat and melt under a vacuum condition of 0.1 MPa, and then stir, continue to heat to 120 to 130°C, and dehydrate for 2 hours. Add the dehydrated polyethylene glycol and organic solvent to the reaction bottle, start stirring, mix the diisocyanate and the second catalyst evenly, add them to the dripping device, turn on the condenser, and start heating under the protection of inert gas. When the temperature rises to a certain temperature, start dripping, and complete the dripping within 0.5 hours, while continuing to heat, keep warm for reaction, and then continue to heat, keep warm for reaction, to generate a prepolymer;

[0082] Then, the monohydric alcohol prepared in step (1) is added, the inert gas is continuously introduced, the temperature is continuously raised, and the reaction is carried out at a temperature of 60 to 100° C., and the molar ratio of the hydroxyl group in the monohydric alcohol to the isocyanate group in the diisocyanate is (1 to 1.2):1.

[0083] After the reaction is completed, the reaction solution is distilled under reduced pressure to remove the solvent, and the obtained product is the polymer.

[0084] The product was characterized by liquid membrane infrared spectroscopy.

[0085] In a specific embodiment, the structural formula of the epoxidized poly-alpha-olefin is shown in Formula III:

[0086]

[0087] Wherein, R1 is a straight-chain alkyl group or a branched-chain alkyl group having 1 to 30 carbon atoms; and n is an integer ≥1.

[0088] Specifically, R1 is a straight-chain alkyl group having 1 to 30 carbon atoms. For example, the carbon number of R1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30. More preferably, R1 is a straight-chain alkyl group having 1 to 14 carbon atoms.

[0089] Specifically, n is 1 or 2.

[0090] More specifically, the epoxidized polyalphaolefin used in the following embodiments includes:

[0091]

[0092] In a specific embodiment, the synthesis route of the epoxidized polyalphaolefin III is as follows:

[0093] 1) α-olefin monomer undergoes polymerization reaction to obtain poly-α-olefin, and the synthesis route is as follows:

[0094]

[0095] 2) Polyalphaolefin is oxidized to generate epoxidized polyalphaolefin, and the synthesis route is as follows:

[0096]

[0097] In a specific embodiment, the preparation method of the epoxidized poly-alpha-olefin is as follows:

[0098] 1) Refining of α-olefins: α-olefins are subjected to reduced pressure distillation, and then the distillation product is eluted through a glass column filled with activated neutral alumina, thereby removing impurities in the α-olefins that affect the activity of the catalyst, especially removing oxygen-containing impurities such as water, long-chain fatty alcohols, and long-chain fatty ethers mixed in the α-olefins. The elution process is carried out in a nitrogen glove box or under nitrogen protection by Schlenk technology. The activation method of neutral alumina is to bake at 600°C in a muffle furnace for 4 hours.

[0099] 2) Preparation of poly-alpha olefins: First, heat the polymerization reactor to above 100°C, vacuum bake for 1 to 2 hours, and replace it with high-purity nitrogen several times to remove water and oxygen impurities in the reactor. Then, adjust the temperature of the reactor to a reaction temperature of 40 to 120°C through the jacket cooling water circulation, add the refined alpha olefin and part of the co-catalyst, stir for 10 to 60 minutes, and then add the metallocene compound and the remaining co-catalyst dissolved in an inert solvent such as toluene to the polymerization reactor. The concentration of the metallocene compound in the reaction system is 0.01 to 1 mmol / L (in terms of transition metal), and the molar ratio of the metal ion in the co-catalyst to the transition metal contained in the metallocene compound is 1 to 1000:1. Open the nitrogen valve and fill the nitrogen pressure to 0.1 to 1.0 MPa for reaction. During the reaction, the pressure in the reactor is kept constant by adding nitrogen, and the reaction temperature is coordinated and controlled by the jacket heat transfer oil and the coil cooling water in the reactor. After the polymerization reaction is completed, the vent pipe is opened to release the pressure, the crude product is discharged from the polymerization reactor, acidified ethanol is added to the crude product to terminate the reaction, 3wt% of activated white clay is added to the obtained product to adsorb and remove the catalyst residue, and then pressure filtration is performed to obtain a filtrate, the obtained filtrate is subjected to reduced pressure distillation to remove the solvent and unreacted monomers, and the corresponding dimer and trimer fractions are collected at a certain vacuum degree and different temperatures, thereby obtaining a poly-alpha olefin containing an unsaturated double bond.

[0100] 3) Preparation of epoxidized poly-alpha-olefin: Place the dimer or trimer of poly-alpha-olefin prepared by the above preparation method in a reaction bottle, add water, sodium bicarbonate and solvent and stir vigorously, cool to below 0°C in an ice water bath, slowly add the oxidant in batches to the reaction bottle and stir to react (at this time, control the reaction liquid temperature below 0°C), and after the oxidant is added, naturally warm to room temperature and continue to stir to react for 1 to 7 days.

[0101] After the reaction was completed, the reaction solution was filtered and the solvent was removed by rotary evaporation (40° C., vacuum degree 10 KPa), and then purified by chromatography column with the eluent being petroleum ether / ethyl acetate with a volume ratio of 10:1, to finally obtain epoxidized poly-alpha-olefin.

[0102] Example 1

[0103] This embodiment provides a more specific method for preparing poly-alpha-olefin.

[0104] In this preparation method, the main catalyst is a metallocene compound with the structural formula:

[0105] The α-olefin is 1-decene, the co-catalyst is methylaluminoxane, the solvent is toluene, the concentration of the metallocene compound in the reaction system is 0.3 mmol / L (in terms of Zr), the concentration of methylaluminoxane in the reaction system is 60 mmol / L, the amount of 1-decene added is 600 mL, the amount of toluene added is 200 mL, the reaction temperature is 60°C, and the reaction pressure is 0.1 MPa. The reaction is terminated after 1 hour of reaction, and the obtained filtrate is collected at a vacuum degree of 0.8 torr to obtain a dimer fraction C at 110-135°C. 20 H 40 , collect the trimer fraction C at 150-170°C 30 H 60 .

[0106] Example 2

[0107] This embodiment provides a more specific method for preparing poly-alpha-olefin.

[0108] In the preparation method, the alpha olefin is 1-octene, the main catalyst is a metallocene compound, the structural formula of the metallocene compound is the same as that in Example 1, the cocatalyst is methylaluminoxane, the solvent is toluene, the concentration of the metallocene compound in the reaction system is 0.3mmol / L (in terms of Zr), the concentration of methylaluminoxane in the reaction system is 60mmol / L, the amount of 1-octene added is 600mL, the amount of toluene added is 200mL, the reaction temperature is 60°C, and the reaction pressure is 0.1MPa. The reaction is terminated after 1h of reaction, and the obtained filtrate is collected at a vacuum degree of 0.8torr to obtain a dimer fraction C at 100-125°C. 16 H 32 , collect the trimer fraction C at 135-155°C 24 H 48 .

[0109] Example 3

[0110] This embodiment provides a more specific method for preparing epoxidized poly-alpha olefin III-1, the structural formula of the epoxidized poly-alpha olefin is:

[0111]

[0112] Wherein, the polyalphaolefin of formula II adopts the polyalphaolefin dimer C prepared in Example 1 20 H 40 The solvent is acetone, the oxidant is potassium peroxymonosulfonate, the polyalphaolefin is 60g, the potassium peroxymonosulfonate is 263g, the sodium bicarbonate is 110g, the water is 240g, the acetone is 150g, the reaction temperature is room temperature, and the reaction time is 6d. After post-treatment, the epoxidized polyalphaolefin C is obtained. 20 H 40 O52g, the yield is 86.7%.

[0113] 1 H-NMR (400MHz, deuterated toluene): δ3.05 (2H, d, J = 4.1Hz), 1.45-1.54 (8H, m), 1.19-1.33 (24H, m), 0.83-0.89 (6H, m). The resonance absorption peak at δ3.05 shows that the presence of epoxy groups in the epoxide molecular structure causes the surrounding 2H to move to the low field and increase the chemical shift.

[0114] Example 4

[0115] This embodiment provides a more specific method for preparing epoxidized poly-alpha olefin III-2, the structural formula of which is:

[0116]

[0117] Wherein, the polyalphaolefin of formula II is the polyalphaolefin trimer C prepared in Example 1. 30 H 60 The solvent is acetone, the oxidant is potassium peroxymonosulfonate, the polyalphaolefin is 66g, the potassium peroxymonosulfonate is 250g, the sodium bicarbonate is 125g, the water is 300g, the acetone is 200g, the reaction temperature is room temperature, and the reaction time is 6d. After post-treatment, the epoxidized polyalphaolefin C is obtained. 30 H 60 O53.5g, yield is 81.1%.

[0118] 1 H-NMR (400MHz, deuterated toluene): δ3.08 (2H, d, J = 4.1Hz), 1.61 (2H, d, J = 8.3Hz), 1.52 (2H, t, J = 6.7Hz), 1.48 (2H, tt, J = 7.1, 6.7Hz), 1.18-1.31 (39H, m), 0.83-0.90 (9H, m), 0.80 (4H, q, J = 7.2Hz). The resonance absorption peak at δ3.08 shows that the presence of epoxy groups in the epoxide molecular structure causes the surrounding 2H to move to the low field and increase the chemical shift.

[0119] Example 5

[0120] This embodiment provides a more specific method for preparing epoxidized poly-alpha olefin III-3, the structural formula of the epoxidized poly-alpha olefin is:

[0121]

[0122] Wherein, the polyalphaolefin of formula II is the unsaturated polyalphaolefin dimer C prepared in Example 2. 16 H 32The solvents used were acetone and acetonitrile, the oxidant was potassium peroxymonosulfonate, the polyalphaolefin was 135 g, the potassium peroxymonosulfonate was 500 g, the sodium bicarbonate was 225 g, the water was 600 g, the acetone was 200 g, the acetonitrile was 200 g, the reaction temperature was room temperature, and the reaction time was 6 days. After post-treatment, epoxidized polyalphaolefin C was obtained. 16 H 32 O 119 g, yield 88.1%.

[0123] 1 H-NMR (400MHz, deuterated toluene) δ3.05 (2H, d, J = 4.1Hz), 1.45-1.51 (8H, m), 1.17-1.32 (16H, m), 0.87 (6H, t, J = 7.0Hz). The resonance absorption peak at δ3.05 shows that the presence of epoxy groups in the epoxide molecular structure causes the surrounding 2H to move to the low field and increase the chemical shift.

[0124] Example 6

[0125] This embodiment provides a more specific method for preparing epoxidized poly-alpha olefin III-4, the structural formula of which is:

[0126]

[0127] Wherein, the polyalphaolefin of formula II is the polyalphaolefin trimer C prepared in Example 2 24 H 48 The solvents used were acetone and acetonitrile, the oxidant was potassium peroxymonosulfonate, the polyalphaolefin was 120 g, the potassium peroxymonosulfonate was 465 g, the sodium bicarbonate was 205 g, the water was 600 g, the acetone was 200 g, the acetonitrile was 200 g, the reaction temperature was room temperature, and the reaction time was 6 days. After post-treatment, epoxidized polyalphaolefin C was obtained. 24 H 48 O 104.5 g, yield 87.1%.

[0128] 1 H-NMR (400MHz, deuterated toluene) δ3.07 (2H, d, J = 4.1Hz), 1.60 (2H, d, J = 8.3Hz), 1.52 (2H, t, J = 6.7Hz), 1.48 (2H, tt, J = 7.1, 6.7Hz), 1.16-1.33 (27H, m), 0.87 (9H, t, J = 7.0Hz), 0.80 (4H, q, J = 7.2Hz). The resonance absorption peak at δ3.07 shows that the presence of epoxy groups in the epoxide molecular structure causes the surrounding 2H to move to the low field and increase the chemical shift.

[0129] Example 7

[0130] This embodiment provides a more specific method for preparing a polymer.

[0131] Wherein, in step (1), the epoxidized polyalphaolefin III-1 is prepared by the preparation method in Example 3, with an amount of 42 g (0.142 mol), the carboxylic acid compound is lauric acid (dodecanoic acid), with an amount of 31 g (0.155 mol), the first catalyst is hexadecyltrimethylammonium chloride, with an amount of 0.05 g, the reaction temperature is first raised to 120°C, kept warm for 2 hours, and then raised to 140°C, and the reaction end point is lower than the acid value below 16 mg KOH / g.

[0132] In step (2), the molecular weight of polyethylene glycol is 10000, the amount of dehydrated polyethylene glycol is 400g (0.04mol), methyl ethyl ketone and acetone are used as organic solvents, and the amounts are 20g and 5g respectively, the diisocyanate is isophorone diisocyanate (IPDI) is used, and the amount is 22.5g (0.10mol), the second catalyst is dibutyltin dilaurate (DBLT), and the amount is 0.02g, the dropping temperature of isophorone diisocyanate (IPDI) and dibutyltin dilaurate is 70°C, the reaction temperature is first 80°C, and the reaction is kept warm for 3h, and then the temperature is continued to be raised to 85°C and the reaction is kept warm for 3h, and finally 73g of the monohydric alcohol prepared in the above step (1) is added, the temperature is raised to 90°C, and the reaction is kept warm for 2h, and nitrogen is used as the inert gas.

[0133] The polymer sample prepared in this example was subjected to infrared analysis using a liquid film method and a Bruker Tensor27 Fourier transform infrared spectrometer to obtain an infrared spectrum of the sample, as shown in FIG. Figure 1 shown.

[0134] FTIR:3342cm -1 (v s NH),2881cm -1 (v s -CH2-),1717cm -1 (v s C=O),1462cm -1 (δ-CH2-),

[0135] 1284cm -1 (v as CO),1099cm -1 (v s CO),844cm -1 (γ-CH2-, -CH3). It can be seen that at 2200-2300cm -1 There is no obvious absorption peak in the range of , indicating that the -NCO group has been completely grafted.

[0136] Example 8

[0137] This embodiment provides a more specific method for preparing a polymer.

[0138] Wherein, in step (1), the epoxidized polyalphaolefin III-1 is prepared by the preparation method in Example 3, with an amount of 42 g (0.142 mol), the carboxylic acid compound is 6-heptene-1-acid, with an amount of 20 g (0.156 mol), the first catalyst is hexadecyltrimethylammonium chloride, with an amount of 0.05 g, the reaction temperature is first raised to 120°C, kept warm for reaction for 2 hours, and then raised to 140°C, and the reaction end point is lower than the acid value below 18 mg KOH / g.

[0139] In step (2), the molecular weight of polyethylene glycol is 10000, the amount of dehydrated polyethylene glycol is 400g (0.04mol), the organic solvent is methyl ethyl ketone, the amount is 25g, the diisocyanate is isophorone diisocyanate (IPDI), the amount is 22.5g (0.10mol), the second catalyst is dibutyltin dilaurate (DBLT), the amount is 0.02g, the dropping temperature of isophorone diisocyanate (IPDI) and dibutyltin dilaurate is 70°C, the reaction temperature is first 80°C, the temperature is kept at 85°C for 3h, the temperature is continued to rise to 85°C, the temperature is kept at 85°C for 3h, and finally 73g of the monohydric alcohol prepared in the above step (1) is added, the temperature is raised to 90°C, the temperature is kept at 90°C for 2h, and the inert gas is nitrogen.

[0140] The polymer sample prepared in this example was subjected to infrared analysis using a liquid film method and a Bruker Tensor27 Fourier transform infrared spectrometer to obtain an infrared spectrum of the sample, as shown in FIG. Figure 2 shown.

[0141] FTIR:3522cm -1 (v s NH),2875cm -1 (v s -CH2-),1718cm -1 (v s C=O),1645cm -1 (v s C=C),1470

[0142] cm -1 (δ-CH2-),1245cm -1 (v as CO),1112cm -1 (v s CO),841cm -1 (γ-CH2-, -CH3).

[0143] It can be seen that at 2200-2300cm -1 There is no obvious absorption peak in the range of 1645cm -1 The characteristic absorption peak of C=C indicates that the double bond has been grafted onto the polymer.

[0144] Example 9

[0145] This embodiment provides a more specific method for preparing a polymer.

[0146] Wherein, in step (1), the epoxidized poly-alpha-olefin III-2 is prepared by the preparation method in Example 4, with an amount of 62 g (0.142 mol), the carboxylic acid compound is β-carboxyethyl acrylate (β-CEA), with an amount of 24.5 g (0.170 mol), the first catalyst is hexadecyltrimethylammonium chloride, with an amount of 0.05 g, and the inhibitor p-hydroxyanisole is added in an amount of 50 mg. The reaction temperature is first raised to 110° C., kept warm for 2 hours, and then raised to 120° C. The reaction end point is lower than the acid value lower than 22 mgKOH / g.

[0147] In step (2), the molecular weight of polyethylene glycol is 10000, the amount of dehydrated polyethylene glycol is 400g (0.04mol), methyl ethyl ketone and acetone are used as organic solvents, and the amounts are 20g and 5g respectively, the diisocyanate is isophorone diisocyanate (IPDI) is used, and the amount is 22.5g (0.10mol), the second catalyst is dibutyltin dilaurate (DBLT), and the amount is 0.02g, the dropping temperature of isophorone diisocyanate (IPDI) and dibutyltin dilaurate is 70°C, the reaction temperature is first 80°C, and the reaction is kept warm for 3h, and then the temperature is continued to be raised to 85°C, and the reaction is kept warm for 3h, and then 86.5g of the monohydric alcohol prepared in the above step (1) is added, the temperature is raised to 90°C, and the reaction is kept warm for 2h, and the inert gas is nitrogen.

[0148] The polymer sample prepared in this example was subjected to infrared analysis using a liquid film method and a Bruker Tensor27 Fourier transform infrared spectrometer to obtain an infrared spectrum of the sample, as shown in FIG. Figure 3 shown.

[0149] FTIR:3439cm -1 (v s NH),2889cm -1 (v s -CH2-),1728cm -1 (v s C=O),1640cm -1 (vs C=C),1470

[0150] cm -1 (δ-CH2-),1285cm -1 (v as CO),1108cm -1 (v s CO),836cm -1 (γ-CH2-, -CH3).

[0151] It can be seen that at 2200-2300cm -1 There is no obvious absorption peak in the range of 1640 cm -1 The characteristic absorption peak of C=C indicates that the double bond has been grafted onto the polymer.

[0152] Example 10

[0153] This embodiment provides a more specific method for preparing a polymer.

[0154] Wherein, in step (1), the epoxidized poly-alpha olefin III-3 is prepared by the preparation method in Example 5, with an amount of 34 g (0.142 mol), the carboxylic acid compound is palmitic acid (hexadecanoic acid), with an amount of 40 g (0.156 mol), the first catalyst is hexadecyltrimethylammonium chloride, with an amount of 0.05 g, the reaction temperature is first raised to 120°C, kept warm for 2 hours, and then raised to 140°C, and the reaction end point is lower than the acid value below 16 mg KOH / g.

[0155] In step (2), the molecular weight of polyethylene glycol is 6000, the amount of dehydrated polyethylene glycol is 240g (0.04mol), methyl ethyl ketone and acetone are used as organic solvents, and the amounts are 5g and 5g respectively, the diisocyanate is hexamethylene diisocyanate (HDI), and the amount is 17g (0.10mol), the second catalyst is dibutyltin dilaurate (DBLT), and the amount is 0.02g, the dropping temperature of hexamethylene diisocyanate (HDI) and dibutyltin dilaurate is 70°C, the reaction temperature is first 80°C, and the reaction is kept warm for 2h, and then the temperature is continued to be raised to 85°C, and the reaction is kept warm for 2h, and then 74g of the monohydric alcohol prepared in the above step (1) is added, the temperature is raised to 90°C, and the reaction is kept warm for 2h, and the inert gas is nitrogen.

[0156] The polymer sample prepared in this example was subjected to infrared analysis using a liquid film method and a Bruker Tensor27 Fourier transform infrared spectrometer. According to the spectrum analysis, 3369 cm -1 (v s NH),2878cm-1 (v s -CH2-),1725cm -1 (v s C=O),1466cm -1 (δ-CH2-),1258cm -1 (v as CO),1111cm -1 (v s CO),845cm -1 (γ-CH2-, -CH3). It can be seen that at 2200-2300cm -1 There is no obvious absorption peak in the range of , indicating that the -NCO group has been completely grafted.

[0157] Embodiment 11

[0158] This embodiment provides a more specific method for preparing a polymer.

[0159] Wherein, in step (1), the epoxidized polyalphaolefin III-4 is prepared by the preparation method in Example 6, with an amount of 50 g (0.142 mol), the carboxylic acid compound is 2-isooctanoic acid, with an amount of 22 g (0.153 mol), the first catalyst is hexadecyltrimethylammonium chloride, with an amount of 0.05 g, the reaction temperature is first raised to 120°C, kept warm for reaction for 2 hours, and then raised to 140°C, and the reaction end point is lower than the acid value below 16 mg KOH / g.

[0160] In step (2), the molecular weight of polyethylene glycol is 6000, the amount of dehydrated polyethylene glycol is 240g (0.04mol), the organic solvent is methyl ethyl ketone, the amount is 10g, the diisocyanate is 4,4'-dicyclohexylmethane diisocyanate (HMDI), the amount is 26.5g (0.10mol), the second catalyst is dibutyltin dilaurate (DBLT), the amount is 0.02g, the dropping temperature of 4,4'-dicyclohexylmethane diisocyanate (HMDI) and dibutyltin dilaurate is 70°C, the reaction temperature is first 80°C, the temperature is kept at 85°C for 2h, the temperature is continued to rise to 85°C, the temperature is kept at 85°C for 2h, and then 72g of the monohydric alcohol prepared in the above step (1) is added, the temperature is raised to 90°C, and the temperature is kept at 90°C for 2h.

[0161] The sample of the polymer prepared in this example was subjected to infrared analysis using a liquid film method and a Bruker Tensor27 Fourier transform infrared spectrometer. The spectrum was analyzed at 3456 cm -1 (v s NH),2883cm -1 (v s -CH2-),1714cm-1 (v s C=O),1459cm -1 (δ-CH2-),1276cm -1 (v as CO),1119cm -1 (v s CO),838cm -1 (γ-CH2-, -CH3). It can be seen that there is no obvious absorption peak in the range of 2200-2300 cm-1, indicating that the -NCO group has been completely grafted.

[0162] Comparative Example

[0163] This comparative example is a comparative example of Example 8.

[0164] The difference is that the monohydric alcohol is 1-octadecyl alcohol, and the amount used is 36.5 g.

[0165] The sample of the polymer prepared in the comparative example was subjected to infrared analysis by liquid film method using a Bruker Tensor27 Fourier transform infrared spectrometer. The spectrum was analyzed. FTIR: 3321 cm -1 (v s NH),2888cm -1 (v s -CH2-),1723cm -1 (v s C=O),1467cm -1 (δ-CH2-),1249cm -1 (v as CO),1105cm -1 (v s CO),847cm -1 (γ-CH2-, -CH3).

[0166] At 2200-2300cm -1 There is no obvious absorption peak in the range of , indicating that the -NCO group has been completely grafted.

[0167] The polymers prepared in Examples 7 to 11 and the comparative examples were subjected to the following performance tests: rheological properties, thickening properties and other performance tests. Figures 4 to 10 and Tables 2-3.

[0168] The test standards or methods are as follows:

[0169] (1) Rheological property measurement: This application uses a rotor rheometer to control different shear rates (0.01-100s -1), and the shear viscosities of the polymers prepared in Examples 7 to 11 and the comparative example at concentrations of 0.5 wt%, 1.0 wt%, 2.0 wt%, and 3.0 wt% were measured respectively.

[0170] The preparation method is to prepare the polymers prepared in Examples 7 to 11 and the comparative example with a mixed solution of water and diethylene glycol monobutyl ether (mass ratio 4:1) into aqueous solutions with concentrations of 0.5wt%, 1.0wt%, 2.0wt% and 3.0wt%, respectively.

[0171] During the test, the sample solution to be tested is prepared and left to stand for 30 minutes to reach equilibrium. At the same time, silicone oil is used to seal the edge of the sample to prevent water evaporation from causing changes in the concentration of the sample solution.

[0172] Measurement results:

[0173] The shear viscosity and shear rate of the polymers prepared in Examples 7 to 11 and Comparative Examples with different concentrations were plotted on the same logarithmic coordinate system. The test results are shown in Figures 4 to 9 ;

[0174] At low shear rates (0.01s -1 and 0.1s -1 ) under different concentrations of the polymers prepared in Examples 7 to 11 and Comparative Examples are shown in Table 2.

[0175] Table 2

[0176]

[0177]

[0178] Generally, the viscosity of the polymer aqueous solution will decrease under shearing action. Once the external shearing action is withdrawn, the solution viscosity will quickly recover to the vicinity of the initial viscosity. This rheological property gives the polymer aqueous solution good thixotropy. The polymers prepared in Examples 7 to 11 of the present invention rely on the association between the multiple hydrophobic chains at the end to form an association network in the solution. This force is a reversible weak force. When the solution system is subjected to a large external shearing force, the hydrophobic force at the end of the polyurethane molecule is broken, which is manifested as the viscosity starting to decrease. When the external force is withdrawn, the hydrophobic chain at the end of the polyurethane molecule will automatically insert into the hydrophobic core of the adjacent micelle to form a micelle aggregate because of its incompatibility with water, which is manifested as the viscosity is restored. Therefore, the polymer aqueous solution system has good thixotropy.

[0179] from Figure 4-9From the above, it can be seen that the shear viscosity of the polymer aqueous solution increases with the increase of concentration. Among them, the viscosity of Examples 7 to 11 at low shear rate changes little with the shear rate, that is, the shear stress and the shear rate are linearly related, which is close to a typical Newtonian fluid state. In this state, the shear rate cannot break the dynamic equilibrium of the association network formed between the hydrophobic segments, that is, the association network cannot be destroyed by the shear force. Therefore, the polymer aqueous solution presents a Newtonian fluid state at low shear rate. As the shear rate increases, the shear force increases the deassociation rate, the dynamic equilibrium of the association network is broken, and the structure is destroyed, resulting in shear thinning of the polymer aqueous solution at high shear rate. By comparing Examples 7 to 11 and the comparative example, it can be seen that in the comparative example, 1-octadecyl alcohol is used for grafting onto polyurethane, and there is only one hydrophobic chain at the end of the polyurethane molecule, which makes it difficult to form a dense hydrophobic association network and is easily destroyed by shear force. Therefore, the corresponding aqueous solution exhibits shear thinning behavior at a low shear rate. In Examples 7 to 11, epoxidized poly-alpha-olefins are reacted with other carboxylic acids for ring-opening and then grafted with polyurethane. The obtained polyurethane molecules have at least 3 hydrophobic chains at the end, have stronger hydrophobic association in aqueous solution, and can form a more complete hydrophobic association network.

[0180] In addition, from the perspective of thickening efficiency, the data in Table 2 show that under the conditions of the same thickener concentration and shear rate, the shear viscosity of the polymer aqueous solution of Examples 7 to 11 is significantly higher than that of the comparative example, which indicates that the hydrophobic association formed between the multiple hydrophobic chains at the ends of the polyurethane thickener molecules is greater, and the high density of the formed association network is conducive to improving the thickening efficiency. Compared with the comparative example, Examples 7 to 11 can achieve the same thickening effect at a lower dosage. In the comparative example, because there is only one hydrophobic side chain on both sides of the polyurethane molecule, the hydrophobic association effect is obviously not as good as that of Examples 7 to 11, and a higher dosage is required to achieve the same thickening effect.

[0181] (2) Thickening performance test:

[0182] The test object is JF1025 water-based acrylic resin emulsion. JF1025 water-based acrylic resin emulsion is prepared by emulsion polymerization of acrylic ester monomers. It has the appearance of a milky white translucent liquid and a solid content of 42±1%. It is a film-forming resin used in quick-drying wood coatings and is provided by Zibo Jiafeng Chemical Technology Development Co., Ltd.

[0183] The test method is to add the polymers prepared in Examples 7 to 11 and the comparative example to the JF1025 aqueous acrylic resin emulsion as a thickener under high-speed dispersion, and the fixed addition amount of the polymer is 0.25wt%. Then, according to the above method, different shear rates are controlled at room temperature (25±1°C) to measure the shear viscosity of the JF1025 aqueous acrylic resin emulsion without adding a thickener and with adding different thickeners.

[0184] Test results: The shear viscosity and shear rate of the JF1025 aqueous acrylic resin emulsion without thickener and with 0.25 wt% of the polymer prepared in Examples 7 to 11 and the comparative example as thickener were plotted on the same logarithmic coordinate system. The test results are shown in Fig.10 , at low shear rates (0.01s -1 and 0.1s -1 The shear viscosity under ) is shown in Table 3.

[0185] Table 3

[0186]

[0187] from Fig.10 From the rheological test, the JF1025 emulsion without any thickener showed obvious shear thinning characteristics, and the viscosity decreased significantly with the increase of shear rate. After adding the comparative polymer, the JF1025 emulsion can maintain a viscosity of 0.1s -1 The viscosity decreases slowly before the shear rate of , and then the shear rate increases to further destroy the hydrophobic association network, and the viscosity of the emulsion system also begins to decrease significantly. After adding the polymers of Examples 7 to 11, the viscosity of the JF10258 emulsion decreases slowly with the increase of the shear rate, especially under the previous low shear rate conditions, the corresponding JF1025 emulsion viscosity changes very little with the shear rate, and its shear stress and shear rate are approximately linear, close to the Newtonian fluid state. This is because Examples 7 to 11 introduce multiple hydrophobic side chains at the ends of the polyurethane molecules, which is conducive to multi-point association to form a denser hydrophobic association network. When used in acrylic emulsion systems, it can significantly reduce the amplitude of shear thinning, which is conducive to maintaining viscosity at high shear rates to avoid splashing due to too thin viscosity during construction. Moreover, the more hydrophobic side chains at the ends of the molecules and the higher the carbon number of the side chains, the greater the strength of the hydrophobic association network formed, and the stronger the resistance to shear force, which is reflected in the rheological properties, that is, maintaining a higher shear viscosity at high shear strength.

[0188] In addition, from the perspective of thickening efficiency, the data in Table 3 show that under the same thickener concentration and shear rate conditions, the JF1025 emulsion to which 0.25 wt % of the polymer of Examples 7 to 11 is added has a higher viscosity. It is believed that the polymers prepared in Examples 7 to 11 have a higher thickening efficiency than the comparative example, and the same thickening effect can be achieved at a lower dosage.

[0189] (3) Varnish preparation and other performance tests

[0190] The polymer prepared in Example 7 was compared with the commercially available polyurethane thickener RM-8W to prepare a water-based wood varnish, wherein the formula of the water-based wood varnish is shown in Table 1:

[0191] Table 1

[0192] Components Dosage / g JF1025 water-based acrylic resin emulsion 66 Film-forming aid (DPM:DPnB=1:1) 7.5 Wetting agent BYK-346 0.5 Defoamer BYK-028 0.1 Thickener 0.2 water 25.7

[0193] Spray the first coat of varnish as shown in the above table on the wood, dry it at room temperature for 24 hours, and after polishing, spray the second coat of varnish, dry it at room temperature for 7 days, and test the water resistance of the paint film respectively by using the room temperature immersion method (GB / T 23999-2009). At the same time, observe and record the state of the paint film during the spraying process. The polymer prepared in Example 7 and the commercially available polyurethane thickener RM-8W are used in the same amount of spraying for preparing water-based wood varnish.

[0194] The wet film appearance of the polymer of Example 7 and the commercially available polyurethane thickener RM-8W prepared water-based wood varnish after spraying is compared. After spraying, the varnish film of the polymer prepared in Example 7 is more transparent and does not appear milky white, while the coating surface of the varnish added with the RM-8W thickener is milky white after spraying, indicating that the wet film permeability of the water-based wood varnish prepared by the polymer prepared in Example 7 is better. When constructing the spray sample, if the wet film is not transparent, it greatly increases the difficulty of observing and controlling the color, which is not conducive to the coloring of water-based paints and cannot achieve the same coloring effect as solvent-based paints. For the water resistance test after 7 days, both the water-based varnish film with the polymer prepared in Example 7 showed slight whitening. The varnish film with the polymer prepared in Example 7 recovered faster and completely returned to normal within 10 minutes, while the varnish film with the RM-8W thickener needed 30 minutes to return to normal, indicating that the polymer prepared in Example 7 can improve the water resistance when used as a thickener in water-based wood paint.

[0195] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A polymer formed by polymerization of the following components, characterized in that: 1) at least one monohydric alcohol, wherein the monohydric alcohol comprises one or both of a compound of formula Ⅴ1 and a compound of formula Ⅴ2: 、 ; Wherein, R1 is a straight chain alkyl or branched chain alkyl having 6 to 30 carbon atoms; n is 1 or 2; R2 is H 23 C 11 -、H 31 C 15 -、H 11 C6- or ; Or R2 is ; 2) at least one polyether polyol; 3) At least one diisocyanate.

2. The polymer according to claim 1, characterized in that The monohydric alcohol is a ring-opening reaction product of an epoxidized poly-alpha-olefin and a carboxylic acid compound.

3. The polymer according to claim 2, characterized in that The molar ratio of the carboxylic acid compound to the epoxidized poly-alpha-olefin is (1-1.2):1; and / or, the reaction temperature is 90-140°C; And / or, the reaction system includes a first catalyst; the first catalyst is a quaternary ammonium salt compound.

4. The polymer according to claim 1, characterized in that The polyether polyol includes polyethylene glycol with a molecular weight of 400-20000 g / mol.

5. The polymer according to claim 1, characterized in that The diisocyanate is a C1-C20 straight-chain alkyl, branched-chain alkyl, a cyclic alkyl with or without a side chain, a C1-C20 benzene ring or an aromatic condensed ring diisocyanate.

6. A method for preparing a polymer as claimed in any one of claims 1 to 5, characterized in that: The steps include: 1) Polyether polyol and diisocyanate react to form a prepolymer; 2) The prepolymer is then contacted with the monohydric alcohol to generate the polymer.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the monohydric alcohol to the isocyanate group in the prepolymer is (1-1.2):1; And / or, the reaction system includes a second catalyst; the second catalyst is one or more selected from dibutyltin dilaurate, stannous octoate or an organic bismuth catalyst; And / or, the reaction system further comprises an organic solvent; the organic solvent is a ketone; And / or, the reaction temperature is 60-100°C.

8. The preparation method according to claim 6, characterized in that: The degree of polymerization of the prepolymer formed by the polyether polyol and the diisocyanate is 2-20.

9. Use of a polymer as claimed in any one of claims 1 to 5 or a polymer prepared by the preparation method as claimed in any one of claims 6 to 8 as a thickener in a film-forming system containing an aqueous resin.

10. The use according to claim 9, characterized in that The water-based resin is a water-based acrylic resin, a water-based polyurethane resin, a water-based polyurethane-acrylate resin, a water-based light-curable acrylic resin, a water-based light-curable polyurethane resin or a water-based light-curable polyurethane-acrylate resin; And / or, the film-forming system containing the water-based resin includes one or more of water-based paint, water-based ink or water-based adhesive; And / or, based on the mass of the water-based resin, the amount of the polymer is 0.1-1.0 wt%.

Citation Information

Cited By

  • UV printing ink adhesion promoter for packaging film and preparation method of UV printing ink adhesion promoter

    CN121449513A